Maternal birth satisfaction among postnatal women in Bhaktapur of Nepal - Khayamali, Rameswori; Joshi, Padam Raj; Khayamali, Renu; Thagunna, Narendra Singh (Journal of Ayurveda Campus, 2024)
Background: Maternal birth satisfaction is a multi-faceted notion which is concerned with quality of care. It is affected by several socio-demographic and obstetric factors. A mother’s satisfaction with childbirth facilities can have a great impact on her physical and mental health and capacity to bond with her baby as well. The study aimed to assess the level of maternal birth satisfaction among postnatal women attending Changunararyan Primary Health Care (PHC), Bhaktapur, Nepal. Materials and Methods: A quantitative descriptive cross-sectional study was assessed among 254 postnatal women of aged 20-45 years and had a baby in the previous 6-12 weeks. Non-probability purposive sampling method was used. Data collection was done by using standardized pre-tested, birth satisfaction scale-revised (BSS-R) tool. Structured interview schedule in Nepali language was carried out. Data analysis was done using SPSS version 16. Chi-square test and regression analysis were used to analyze the relationship between the dependent and independent variables. Results and Discussions: Total mean score of maternal birth satisfaction of postnatal women was 21.85±3.43, which showed that there is moderate satisfaction among the women. The study showed that the majority (86%) of the respondents were satisfied whereas, 14% were unsatisfied with perinatal service delivery. In Pearson’s Chi-square analysis, there was statistically significant association between age (p = 0.03), type of family (p = 0.001), parity (p = 0.02) and getting support during labor and child birth (p = 0.001) and maternal birth satisfaction. In bivariate and multivariate regression analysis, respondents living in the joint family has 4.74 times more likely to have maternal birth satisfaction [AOR=4.74; 95% CI: 1.43-15.76] than respondents living in the nuclear family. Regarding getting support, postnatal women who received support at birth and after birth were 3.525 times more likely to be satisfied [AOR=3.52; 95% CI: 1.24-9.96] than those did not received any support during labor and childbirth. Conclusion: The result concludes that majority of the postnatal women were satisfied with the perinatal delivery service. Age, family type, parity and getting support during labour and childbirth were statistically associated with maternal birth satisfaction. Maternal satisfaction plays significant role in physical and mental health in the postpartum period.